PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI MEDIA AUDIOVISUAL (FILM PENDEK) PADA SISWA KELAS IV SDK ROWOREKE 1 - Maria Floriana Serlin (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to improve poetry writing skills in fourth-grade students at SDK Roworeke 1 using audio-visual learning media in the form of short films. This study employed a qualitative method with a Classroom Action Research (CAR) approach. The subjects were 26 fourth-grade students, consisting of 14 boys and 12 girls. Data collection methods used were tests (learning outcome tests), observations (student and teacher activities), and documentation. Data analysis techniques included quantitative techniques for learning outcomes and qualitative techniques for observational data. The results showed that the use of short audio-visual media can improve students' poetry writing skills. This improvement was demonstrated by the average score of 62.0 in the pre-cycle stage. In the first cycle, the average score increased to 74.5, representing a 12.5-point increase from the pre-cycle stage. Furthermore, in the second cycle, the average score increased to 82.5, representing a 20.5-point increase from the initial score. Thus, the use of innovative learning media tailored to student characteristics can significantly improve learning outcomes and student motivation in writing poetry.